Expressão imuno-histoquímica de IL-17, TGF-β1 e FOXP3 em ganulomas periapicais, cistos radiculares e cistos radiculares residuais - Andrade, Ana Luiza Dias Leite de (2012)
Periapical lesions are chronic inflammatory conditions of periradicular tissues considered direct consequences of infectious diseases resulting from pulp necrosis and subsequent progression to periapical region. The participation of the immune response and bone resorption in the formation of these lesions has been investigated, so that different cell types and cytokines have been identified as contributors to this process. In this perspective, this study aimed to evaluate the immunohistochemical expression of IL-17, TGF-β1 and FoxP3 in periapical granulomas (PGs), radicular cysts (RCs) and residual radicular cysts (RRCs), seeking a better understanding of the etiopathogenesis these periapicopatias. To this end, we selected 20 cases of GPs, 20 CRs and 10 RRCs to undergo morphological analysis and immunohistochemistry for biomarkers above, the latter being performed quantitatively using scores and average percentages of immunostaining for the analysis of IL-17 and TGF- β1, while for the FoxP3 were counted only the positive lymphocytes. The results showed statistically significant differences between TGF-β1 and FoxP3 imunoexpressions, in relation to the periapical lesions studied (p = 0.002, p <0.001, respectively) but not between IL-17 and these (p = 0.355). Furthermore, the analysis of lymphocytes FoxP3-positive revealed significant statistical differences in that refers to the intensity of inflammatory infiltrate (p = 0.003) and also regarding thickness of the epithelial lining (p = 0.009). Finally, it was observed in the case of PGs, strong positive correlation between the amount of FoxP3- positive lymphocytes and the immunohistochemical expression of TGF-β1 (r = 0.755, p<0.001), as well as moderate positive correlation between IL-17 and TGF-β1 imunoexpressions (r = 0.503, p = 0.024). Thus, we can conclude that interactions between Th17 and Treg cells seem to be established at the site of injury, suggesting the involvement of both pro-inflammatory and immunoregulatory cytokines in the pathogenesis of periapical lesions